Effects of dapagliflozin in experimental sepsis model in rats - OKUYAN, BETÜL; ÖZSAVCI, DERYA; ERCAN, FERİHA; ÇAM, MUHAMMET EMİN; BİNGÖL ÖZAKPINAR, ÖZLEM; KAYA, ÖZLEM TUĞÇE; ŞEKERLER, TURGUT; ÖZDEMİR KUMRAL, ZARİFE NİGAR (TURKISH ASSOC TRAUMA EMERGENCY SURGERY, 2018)
BACKGROUND: The aim of this study was to evaluate the possible protective effects of dapagliflozin in an experimental sepsis model in rats. METHODS: Saline (1 mL/kg, p.o.) or dapagliflozin (10 mg/kg, p.o.) was administered to Sprague-Dawley rats for 5 days prior to the surgical procedures. Under anesthesia, sepsis was induced by cecal ligation puncture, while sham control groups underwent laparotomy only. Blood urea nitrogen, creatinine, and glucose levels were measured in serum samples and the levels of malondialdehyde (MDA), glutathione (GSH), myeloperoxidase (MPO), tumor necrosis factor alpha, interleukin 1 beta, caspase 8, and caspase 9 were determined in tissue samples (kidney, liver, and lung). Histological evaluation was also performed. RESULTS: The administration of dapagliflozin in a sepsis model reduced oxidative stress (MDA), increased antioxidant levels (GSH), and reduced inflammation (MPO) in the kidney (p<0.05). Dapagliflozin also decreased oxidative stress (MDA) in lung tissue and decreased inflammation (MPO) in lung and liver tissue (p<0.05). Caspase 8 and 9 levels in kidney, lung, and liver tissue were increased (p< 0.05) in the dapagliflozin group compared with the sepsis group. According to the histopathological results, sepsis was moderately improved in renal tissue and slightly attenuated in lung and liver tissue with the administration of dapagliflozin. CONCLUSION: Dapagliflozin had a preventive effect on sepsis-induced kidney damage, but the protective effect was mild in lung and liver tissue in the present study.
Keywords: Apoptosis; dapagliflozin; inflammation; oxidative stress; sepsis; ACUTE LUNG INJURY; NF-KAPPA-B; CECAL LIGATION; OXIDATIVE STRESS; SYSTEMIC INFLAMMATION; KIDNEY; PIOGLITAZONE; INHIBITION; PUNCTURE; GLUCOSE